Voices from the margins building evidence for inclusive policy responses to Covid 19 in Bangladesh - Centre for Peace and Justice (CPJ), Brac University (Brac University, 2022)
A targeted survey carried out by the Centre for Peace and Justice (CPJ), Brac University on marginalised communities in Bangladesh highlights the need for urgent policy responses to mitigate specific challenges posed by the Covid-19 Pandemic on lives and livelihoods. The survey solicited feedback from 1533 households from three categories of economically disadvantaged marginalised population namely – a) Rural Households, b) Urban Slum Dwellers, and c) Ethnic and religious minority communities. Poor female headed households and households having Persons with Disabilities were considered as two crosscutting groups. Topline findings from this survey include: Respondents from the marginalised communities have been severely impacted by the Pandemic in terms of loss in income, forced reduction in spending, depleting savings, and reduced food consumption. Rural households were found to be the hardest hit. Female headed households were the most affected from reduced food consumption. Education of the ethnic and religious minority family's school-going children was highly affected. There was a spike in domestic violence and child marriage. Multiple strategies were adopted to cope with the adverse effects of the Pandemic. Borrowing cash, changing place of residence, reducing food consumption, dipping into savings and taking up low paying jobs were the most quoted coping strategies. As on June 2021, more than one-fourth of the marginalised households reported receiving some kind of government support packages. A large proportion of the respondents (63%) however expressed skepticism as to whether the economic rebuilding support programmes would be inclusive. Financial assistance was the most sought-after assistance and almost all those needing financial assistance preferred to receive it through mobile banking. Social solidarity among the communities is a bright beacon in these trying times as local community initiatives to enforce health protocols and to support those in need were largely reported, especially by ethnic and religious minorities and the rural poor. A targeted survey carried out by the Centre for Peace and Justice (CPJ), Brac University on marginalised communities in Bangladesh highlights the need for urgent policy responses to mitigate specific challenges posed by the Covid-19 Pandemic on lives and livelihoods. The survey solicited feedback from 1533 households from three categories of economically disadvantaged marginalised population namely – a) Rural Households, b) Urban Slum Dwellers, and c) Ethnic and religious minority communities. Poor female headed households and households having Persons with Disabilities were considered as two crosscutting groups. Topline findings from this survey include: CPJ organized a unique Policy Clinic where a multistakeholder group consisting of academics, researchers, public health experts, bureaucrats, rights activists, journalists and community leaders reviewed and validated the findings.